Working Arrangements for the Welfare and Protection of Adult Victims and Potential Victims of Human Trafficking and Modern Slavery : Guidance issued by the Department of Justice, the Police Service of Northern Ireland and the Health and Social Care Board.: Guidance issued by the Department of Justice, the Police Service of Northern Ireland and the Health and Social Care Board. (2018) - Northern Ireland., Department of Justice; Northern Ireland., Health; Social Care Board; Police Service of Northern Ireland
No abstract available